The Role of Halal Awareness in Moderating the Effect of Content Marketing and Online Customer Review on Purchase Decisions - Ayu Firnanda; Haqiqotus Sa'adah (Airlangga Journal of Innovation Management, 2026)
The increasing use of TikTok Shop and the growing demand for skincare products among Generation Z have significantly influenced consumer purchasing behavior. For Muslim consumers, purchase decisions are shaped not only by digital marketing factors but also by awareness of products' halalness, making it important to examine the role of halal awareness in the digital marketplace. This study aims to analyze the influence of content marketing and online customer reviews on skincare purchase decisions through TikTok Shop among Generation Z consumers in Surabaya and to examine the moderating role of halal awareness. A quantitative approach was employed using a survey method. Data were collected through questionnaires distributed to 115 respondents selected through Purposive sampling and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that content marketing and online customer reviews have a positive and significant effect on purchase decisions, with content marketing emerging as the most influential factor. Halal awareness was found to weaken the influence of both variables on purchase decisions, indicating that Muslim Generation Z consumers carefully consider the halal aspect before making purchases. Therefore, skincare companies should provide informative content, encourage authentic customer reviews, and clearly communicate halal certification and product ingredients.